Clinical Profile of Muco-Cutaneous Lesions in Dengue Fever in Children at a Tertiary Care Hospital - Mohd Irfan Inamdar; Varsha Suresh Ahirrao (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Dengue is arthropod borne viruses, they use mosquitoes as vector. AedesAlbopictus although could be a suitable vector, the Aedesaegypti work as the most efficient carrier, vectors also serve to amplify viral replication.The frequency of Dengue and its complications has increased over the past few years, especially in rural area. Dengue has a wide spectrum of clinical presentation, unpredictable clinical evolution and outcome, especially in children. Subjects and Methods: The study was conducted over a period of two years on Dengue cases in Paediatrics department of Medical College and Research Hospital.Children with fever of acute onset, with clinical featuressuggestive of Dengue fever as described in WHO 2012 Guidelines.Children with age less than 18 years, admitted as Dengue feverbased on clinical features as described in WHO 2012 Guidelines and positive Ns1Ag and/or Dengue IgM. Results: Dengue fever had fewer mucosal manifestations compared to cutaneous manifestations. 144 cases had mucosal manifestations. Scleral Congestion/Conjunctival Haemorrhage was the most common manifestation seen in 69 cases (47.92%),followed by Erythema and Crusting of Lips and Tongue (31.94%) , vesicles on soft palate or throat congestion (29.86%) and Palatal Haemorrhage and Gingival bleeding (11.80%). Conclusion: Flushing is the most common cutaneous manifestation in our study followed by macular rash, petechiae and pruritus. Flushing is an early feature occurring around day 2 of illness, whereas, pruritus is a late manifestation, occurring around day 5 of illness. Thus, Dengue should be strongly considered in any child presenting with fever and flushing.